Case Report: Two cases of recurrences at the suprasternal space and lymph nodes between the sternocleidomastoid and sternohyoid muscles in papillary thyroid carcinoma - Choi, Hae Won; Song, Chang Myeon; Ji, Yong Bae; Tae, Kyung (Frontiers in Surgery, 2024)
Recently, lymph node metastasis to the suprasternal space (SSLN) and lymph nodes between the sternocleidomastoid and sternohyoid muscles (LNSS) have received attention. This article reports two cases of SSLN and LNSS recurrence and emphasizes the need for a thorough evaluation and consideration of the possibility of recurrence in this region. The clinical significance of the prophylactic dissection of SSLN and LNSS remains unclear, and further studies are required to determine its value. Regular follow-up checks of suspicious lymph nodes at SSLN and LNSS, as well as the central and lateral compartments, are recommended after thyroidectomy to detect recurrences and ensure appropriate management.